Toward Sustainable Clean Water: Evaluation of the Patradaya Programme in Rengel Village, Tuban - Widiyastono, M. Hestu (SERUNAI, 2023)
The clean water reservoir construction programme is an important step in improving access to clean water for the community, especially in areas with water crisis. This study evaluated community satisfaction with the construction of clean water reservoirs through the implementation of the Patradaya Programme in 2022 in Rengel Village, Tuban District. Using a quantitative survey method, data was collected from beneficiary respondents. The analysis results showed a high level of satisfaction, with a satisfaction index value of 3.87 and an IKM conversion of 96.72. The quality of service was rated A, and the performance of the service unit was rated as highly satisfactory. The programme was considered successful in creating a positive impact on the Rengel Village community. The policy implications of this evaluation allowed the company to take the right steps in supporting community welfare in a sustainable manner. In conclusion, the 2022 Patradaya Programme in Rengel Village, Tuban Regency received very good ratings from the community, demonstrating congruence with their needs and expectations.